The world in 2050 : four forces shaping civilization's northern future - Smith, Laurence C. (Dutton ; Penguin, 2011)
"A vivid, scientifically based forecast of our planet in forty years, distilling cutting edge research into these world-changing forces: demographic trends; natural resource demand; climate change; globalization"--Jacket flap.